PERANAN STRATEGI DIFERENSIASI PRODUK BERBASIS CREATIVE ENTEPRENENUR UNTUK MENINGKATKAN KEUNGGULAN KOMPETITIF PRODUK - Nawangsih . (UNEJ e-Proceeding)
The research objective was to determine the role of product differentiation strategy based enteprenenur creative and competitive advantages of the product. Research conducted using qualitative descriptive method with case study approach, data collection techniques using snowball sampling through interviews, observation and document study. The results showed that the role of product differentiation strategy based creative entrepreneur is able to be an effective solution to improve the competitive advantage of the product because it can create a new market share and potential to be developed. The competitive advantage of the resulting product is a product of creative design with the theme of environmental awareness and potential of the local area. The implication of the study is to contribute positively to the government to give more attention to the local potential of the region and the presence of young entrepreneurs in creating business opportunities and new, more productive, economically valuable high by empowering the local community as a subject in the business activities undertaken by way of establishing a business partnership.